Pengaruh Latihan Aerobik Terhadap Peningkatan Saturasi Oksigen Pada Pemain Bola Basket Unit Bola Basket Universitas Muhammadiyah Surakarta - Wicaksono, Setyo Adhy, Totok Budi Santoso, S.Fis.,Ftr.,MPH, Yulisna Mutia Sari, SSt.FT., M.Sc () (2015)
Background: A basketball player need good stamina to play, include have good oxygen saturation. Better Oxygen saturation expected more longer ability of players in playing basketball . To get oxygen saturation need necessary exercise routine as aerobic exercise . good exercise increase aerobic oxygen saturation. Objective: This study to know influence aerobic exercise to increase saturation oxygen in a basketball player of basketball the university of muhammadiyah surakarta. methode research: this research use quasi experiment with pretest -- posttest control group design . Sample were17 basketball players as treatment group , and 17 players as control group . aerobic exercise with run for 20 minutes around the basketball court in ums gymnasium with size of 28 meters long and wide field of 15 meters .The measurement of oxygen saturation oxymetri done with. data analysis use comparative wilcoxon signed ranks test and chi square test . results of research, treatment group average pre test with saturation oxygen with 96.06 % and post test to 97.94 % The control group , average saturation oxygen 95.53 % and post test 95.18 % .Based on test aerobic exercise there was difference saturation oxygen between treatment group with control group with p= 0,000. Conclusion: there were Influence aerobic exercise to increase saturation oxygen in a basketball player of basketball the University of Muhammadiyah Surakarta.